(untitled) (Innovative professional education, 2025)
The framework concept of «Education 4.0» and its components have been analyzed, as well as the prospects for its integration into the vocational education system of Ukraine. The main trends changing the global labor market and future workplaces have been identified, along with the relevant skills that will become key and significant for future employers. Conclusions have been drawn about the key directions of «Education 4.0» that can help modernize the vocational education system, making the educational process more flexible, innovative, and aimed at meeting the needs of the modern labor market for highly skilled workers